P-471 Effect of verteporfin, an inhibitor of Hippo signaling pathway, on chemotherapy-induced follicle activation and survival of neonatal mice ovaries in vitro. (30th June 2022) - Dias Nunes, J; Devos, M; Demeestere, I
Abstract: Study question: Does verteporfin, an inhibitor of Hippo signaling pathway, influence mechanisms involved in chemotherapy-induced follicle activation and survival in vitro ? Summary answer: Verteporfin acts directly on cell growth and indirectly on phosphatidylinositol-3-kinase (PI3K) signaling pathway, but does not prevent chemotherapy-induced follicle activation, although moderates 4-hydroperoxycylophosphamide (4HC) gonadotoxicity. What is known already: Cryopreservation of ovarian tissue is an experimental technique aimed at prepubertal patients in need of chemotherapy. To optimize this method, in vitro culture of cryopreserved tissue is being investigated. However, this process leads to a massive loss of primordial follicles due to their spontaneous activation. Inhibition of PI3K pathway, the major signaling pathway involved in follicle activation, is moderately efficient to prevent chemotherapy-induced follicle activation. Recently, the effect of Hippo pathway disruption due to sectioning on follicle activation has been described, suggesting that verteporfin can inhibit Hippo pathway-induced follicle activation. Study design, size, duration: Ovaries collected from post-natal day 3 and/or 4 (PND3/4) mice were used for this study. Whole and cut ovaries were cultured in vitro for 3 hours to validate the effect of verteporfin on Hippo pathway disruption. Whole ovaries were cultured in vitro for 24 and 48 hours to assess the impact of verteporfin and/or chemotherapy (4HC, 10 µM) exposure on primordial follicle activation and survival. At least 3 ovaries were used for each condition. Participants/materials, setting, methods: The inhibitory and toxic effects of verteporfin on whole and cut ovaries were investigated by analysing the expression of genes involved in Hippo and PI3K pathways, as well as in apoptosis (RT-qPCR). The effect of co-treatment with verteporfin and 4HC on follicle activation and survival was assessed by histological analysis (immunohistochemistry and TUNEL staining), gene expression (RT-qPCR) and protein analysis (immunostaining and Western Blot) to investigate signaling pathways, cell proliferation and apoptosis. Main results and the role of chance: The inhibitory effect of verteporfin on Hippo pathway disruption induced by sectioning was achieved on ovaries exposed to 3 µM of verteporfin despite slightly increasing apoptosis at 3 hours of culture. Verteporfin was able to slightly prevent the effect of chemotherapy on Hippo pathway, but its impact was limited by the time of culture. Surprisingly, verteporfin also acted indirectly on PI3K pathway by significantly decreasing the level of downstream phosphorylated proteins. However, in presence of chemotherapy, verteporfin was not sufficient to prevent the effect of 4HC on this pathway. Alone, verteporfin also significantly decreased granulosa cells proliferation, depending on the time of culture: although reducing cell growth at 24 hours of culture, this effect was not observed after 48 hours of in vitro culture. The inhibitor was not able to prevent apoptosis induced by 4HC at 24 hours of culture. However, at 48 hours of culture, the decrease in the number of positive TUNEL follicles in the co-treatment condition compared to ovaries treated with chemotherapy alone suggested a potential positive effect of verteporfin to prevent chemotherapy-induced gonadotoxicity. Limitations, reasons for caution: The main limitation of this study is the experimental model used. Although mouse is a strong and reliable model, it lacks certain characteristics specific to human. Investigating other timepoints of culture and exposition, as well as different doses of verteporfin, might benefit the study. Wider implications of the findings: Our study supports Hippo and PI3K pathways interaction during in vitro follicle activation. Despite verteporfin does not appear to be an inhibitor of interest, testing another Hippo inhibitor or combining Hippo and PI3K pathways inhibitors could be investigated to control follicle activation during in vitro culture of ovarian tissue. Trial registration number: Not applicable